Faith. Vol. 1, Hollywood and Vine - Houser, Jody (Valiant Entertainment LLC, 2016)
By day, Faith Herbert is a pop-culture blogger in L.A. But when she discovers her latent powers, she transforms into Zephyr, a sky-zooming superhero in the Harbinger Renegades. When she notices other heroes go missing in the city, Faith must solve the mystery or face the consequences.